2015
DOI: 10.1038/ncomms10030
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optoelectronic quality of perovskite thin films with hypophosphorous acid for planar heterojunction solar cells

Abstract: Solution-processed metal halide perovskite semiconductors, such as CH3NH3PbI3, have exhibited remarkable performance in solar cells, despite having non-negligible density of defect states. A likely candidate is halide vacancies within the perovskite crystals, or the presence of metallic lead, both generated due to the imbalanced I/Pb stoichiometry which could evolve during crystallization. Herein, we show that the addition of hypophosphorous acid (HPA) in the precursor solution can significantly improve the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
529
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 662 publications
(584 citation statements)
references
References 48 publications
(65 reference statements)
34
529
0
3
Order By: Relevance
“…These peaks are associated with Pb 2+ in the perovskite. It was noteworthy to point out that another pair of peaks with lower binding energies (141.6 and 136.8 eV) with the signature of Pb 0 were detected when the perovskite films were etched by argon ion seen in Figure S3 (Supporting Information) 48, 49. The peaks of Na 1s and K 2p were also observed, confirm the existence of Na + and K + .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…These peaks are associated with Pb 2+ in the perovskite. It was noteworthy to point out that another pair of peaks with lower binding energies (141.6 and 136.8 eV) with the signature of Pb 0 were detected when the perovskite films were etched by argon ion seen in Figure S3 (Supporting Information) 48, 49. The peaks of Na 1s and K 2p were also observed, confirm the existence of Na + and K + .…”
Section: Resultsmentioning
confidence: 74%
“…In this regard, combination of solvent and dopants have been tested, such as: the introduction of different source of metal or the solvent, the utilization of single or mixed solvent,19, 20 a variety of lead salt precursors,21, 22 as well as so‐called engineering step23 or the exotic additive: ionic liquid,24 Lewis base25, 26, 27 or other organic and inorganic additives (MACl,28 Guanidinium,29 water,30, 31 H 3 PO 2 ,32, 33 1,8‐diiodooctane (DIO),34 1‐chloronaphthalene (CN),35 hydroiodic acid (HI),36, 37 aluminum acetylacetonate (Al‐acac 3 ),38 LiI,39 Na + 40 etc. ), which induce the nucleation and crystallization process of perovskite thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Especially, for the low-bandgap perovskite (60% and 80% Sn content) based PV devices, the obtained V OC 's are significantly high given the fact that planar heterojunction-based PV device configuration is generally known to demonstrate low V OC 's in comparison with device architectures incorporating mesoporous charge extraction layers. [35,48,49] The EQEs measured for these devices are lower at higher wavelengths due to lower absorption in the IR absorption compared to that in the visible region (see the Supporting Information, Figure S1) and this could potentially limit the J SC 's that we get in our devices. This problem has been attributed to the presence of MAPb x Sn 1-x Cl 3 up to 33% of the total material in the thin film that does not absorb visible light due to its large bandgap (>3 eV), [50] and the longer wavelength absorption and EQE can be increased by adding molecular iodine into the precursor solution that reduces this pure chloride perovskite phase to below 10%, hence, enhancing the longer Adv.…”
Section: Doi: 101002/adma201604744mentioning
confidence: 99%
“…PDS is capable of measuring 4-5 orders of magnitude dynamic range absorption data that allow for assessing the perovskite semiconductor quality and measuring disorder in terms of Urbach energy "E U " with a higher degree of sensitivity compared to linear absorption measurement techniques. [34][35][36] Urbach energy can be derived from the following expression:…”
Section: Doi: 101002/adma201604744mentioning
confidence: 99%
“…Furthermore, it has been shown that additives to the precursor solution can impact the nucleation rate, morphology, grain size, and crystallinity of the perovskite. Additives, such as polymers, [13] small molecules, [14,15] metal ions, [16] water, [17] or acids, [18][19][20][21][22][23][24] can play a vital role in material quality, enabling improvements in material stability, optoelectronic properties, and photovoltaic performance.Work by Yan et al characterized the 1:1 CH 3 NH 3 I:PbI 2 stoichiometric precursor solution as a colloidal dispersion in a mother solution, rather than a pure solution. [25] When fabricated on planar substrate, this colloidal solution forms films with poor morphology, due to the presence of rodshaped colloids comprised of a soft coordination complex in the form of a lead polyhalide framework.…”
mentioning
confidence: 99%